Productos Naturales: Utilidad y medida de su eficacia en cosmética - de Castro, Astrid (2000)
Having in mínd the preference of consumers for natural of biotecnological materials ín cosmetics, we decided to study some natural raw materials that could constitute a valid, safe and efficient alternative. To do so, we studied: first the moisturizing effect of soja protein fitosterol producer and with inhibitory effect on proteinases (1); second the antipruriginous activity of lipidic residue of barley (2), and third, the effectivity of a sun protector with zinc dioxide, titanium dioxide (blockers), soja protein complex (moisturizing anti-iritative with anti-ozone activity) and lipidic residue of barley as antipruriginous. Several formulationes were designed according to some basic principles(3); and in case of soja protein, the effect was compared with aloe vera, the lipidic residue of cebada has been compared with a placebo, aloe vera and chamomile and finally the effectivity of the sun protector was determined by means of a clinical study.In all cases, non invasive in vivo studies were performed. The results obtained demostrate that: the soja protein hold up the moisturizing effect for more time than aloe vera.The lipidic residue of Barley has a better antipruriginous effect, than the mix of barley and chamomile. The formulation of sun protector offers a safe and effective alternative for the treatment of damaged, sensible and delicate skin.